Facilitation of Crossmodal Integration During Emotional Prediction in Methamphetamine Dependents - Zhang, Zhao; He, Weiqi; Li, Yuchen; Zhang, Mingming; Luo, Wenbo (Frontiers in Neural Circuits, 2020)
Methamphetamine (meth) can greatly damage the prefrontal cortex of the brain and trigger dysfunction of the cognitive control loop, which triggers not only drug dependence but also emotional disorders. The imbalance between the cognitive and emotional systems will lead to crossmodal emotional deficits. Till now, the negative impact of meth dependence on crossmodal emotional processing has not received attention. Therefore, the present study firstly examined the differences in crossmodal emotional processing between healthy controls and meth dependents (MADs) and then investigated the role of visual or auditory-leading cues in the promotion of crossmodal emotional processing. Experiment 1 found that MADs made a visual-auditory integration disorder for fearful emotion, which may be related to the defects in information transmission between the auditory and auditory cortex. Experiment 2 found that MADs had a crossmodal disorder pertaining to fear under visual-leading. But the fearful sound improved the detection of facial emotions for MADs. Experiment 3 reconfirmed that, for MADs, A-leading could more easily induce crossmodal integration immediately than V-leading. These findings provided sufficient quantitative indicators and evidence that meth dependence was associated with crossmodal integration disorders, which in turn was associated with auditory-leading cues enhanced the recognition ability of MADs for complex emotions (all results are available at: https://osf.io/x6rv5/). These results provided a better suggestion for individuals using drugs in order to enhance the cognition for the complex crossmodal emotional integration.